2020
DOI: 10.1073/pnas.1920875117
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent backlighting illuminates the complex visual signals of a social squid in the deep sea

Abstract: Visual signals rapidly relay information, facilitating behaviors and ecological interactions that shape ecosystems. However, most known signaling systems can be restricted by low light levels—a pervasive condition in the deep ocean, the largest inhabitable space on the planet. Resident visually cued animals have therefore been hypothesized to have simple signals with limited information-carrying capacity. We used cameras mounted on remotely operated vehicles to study the behavior of the Humboldt squid, Dosidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Pacific sardine has several spots running along its lateral surface (Figure 1b ), while California market squid produces a large repertoire of stereotyped pigmentation patterns involving stripes and splotches (Hunt et al, 2000 ; Zeidberg, 2004 ). Pigmentation patterning in fish could have signaling value during collective movements, determine group behaviors, facilitate organization, and reinforce unification (Pavlov & Kasumyan, 2000 ), and the same may be true of social squid (Burford & Robison, 2020 ; Hanlon & Messenger, 2018 ). High alignment in both squid and sardine could therefore indicate behavioral convergence in collective motion in these species due to the functional importance of information transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacific sardine has several spots running along its lateral surface (Figure 1b ), while California market squid produces a large repertoire of stereotyped pigmentation patterns involving stripes and splotches (Hunt et al, 2000 ; Zeidberg, 2004 ). Pigmentation patterning in fish could have signaling value during collective movements, determine group behaviors, facilitate organization, and reinforce unification (Pavlov & Kasumyan, 2000 ), and the same may be true of social squid (Burford & Robison, 2020 ; Hanlon & Messenger, 2018 ). High alignment in both squid and sardine could therefore indicate behavioral convergence in collective motion in these species due to the functional importance of information transfer.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of fish species are known to live in groups for at least part of their lives, and many of these species exhibit collective motion (Pavlov & Kasumyan, 2000 ). For squid species that have been studied in sufficient detail (e.g., commercially important, epipelagic, and/or nearshore species), 82% (58 species) are known to form social groups (Burford et al, 2019 ; Burford & Robison, 2020 ; Jereb & Roper, 2010 ). Of these social squids, some are capable of collective motion, as evidenced by video, laboratory, and acoustic studies of group organization and observations of coordinated group movements (Adamo & Weichelt, 1999 ; Benoit‐Bird & Gilly, 2012 ; Hurley, 1978 ; Mather & O’Dor, 1984 ; Moynihan & Rodaniche, 1982 ; Sugimoto & Ikeda, 2012 ; Sugimoto et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, communication through visual signals is widespread in the animals that display various degrees of social behaviours. Many properties of light such as colours, skin patterns, iridescence and bioluminescence have been developed by evolution for intra- or inter-species signalling [ 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 ]. While intra-species communication generally involves social interactions and mating, inter-species communication mediates symbiotic relationships or shapes ecosystem interactions.…”
Section: Hypothesis: Bioluminescence Signalling In the Unicellular Worldmentioning
confidence: 99%
“…Luminescence is a common physical phenomenon to create light, which was discovered among more than 10,000 species, i.e., bacteria, fungi, protists and animals (Desjardin et al, 2008;Haddock et al, 2010;Meighen, 1991). Luminescence is a kind of specific communication approaches for signaling, such as alarming predators (Burford & Robison, 2020), trapping prey (Verdes & Gruber, 2017;Wainwright & Longo, 2017) and attracting mates (Ellis & Oakley, 2016). During the past years, it was found that fluorescent proteins (FPs) and bioluminescent systems are responsible for induction of most native luminescence (Kim & Paulmurugan, 2021).…”
Section: Introductionmentioning
confidence: 99%